Entity Sentiment Analysis with the Netray Monitoring Tool in Indonesian Online News Media on the Fuel Price Hike - Tjahyana, Lady Joanne; Lesmana, Fanny (Information & Media, 2024)
Introduction. This study aims to find the sentiment in Indonesian online news media surrounding the government’s decision to increase fuel prices on September 3rd, 2022. Additionally, this study investigates the discourses of situational crisis communication strategies (SCCT) around the critical entities in each positive and negative sentiment. Method. The researchers conduct entity sentiment analysis by collecting news data, identifying the primary entities, and analyzing the sentiment using the Netray monitoring tool. The researchers employ critical discourse analysis to find how the media portrays the SCCT strategies surrounding the key entities in positive and negative sentiment news. Analysis. The dominant strategies for positive sentiment are rebuild and bolstering strategies, whereas for negative sentiment, diminish strategies prevail. Results. At the outset, the discourses reflect the strategies positively encompassing the primary entity “price” as the representation of government policy. The subsequent discourses depict the strategies negatively, focusing on “Pertamina” as responsible for the policy’s operational aspects. Positive discourses for “Pertamina” are consistently distributed, adeptly constructing a positive image in the news. The discourses highlight the “fishermen” as a prominent group to convey both positive and negative sentiments. Conclusions. The government and PT Pertamina should monitor the narrative surrounding primary entities as it can enhance or harm their reputation.
Keywords: entity sentiment analysis; fuel price hike; Netray; SCCT; media discourse